Life Skills Education to Improvement of Teenager’s Knowledge, Attitude, Self-efficacy and Risk Health Behavior (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
IDHS data shows adolescent risky behaviors such as smoking, alcohol, drugs and free sex tend an increasing from year to year. The purpose of this study was to analyze the influence of life skills education on adolescents’ knowledge, attitudes, self-efficacy and prevention of health risk behaviors.This study was a quasi-experimental design with non-equivalent pre-test post-test control group. Of 28 and 60 adolescents at the villages of Sembukan and Sukoharjo, Wonogiri were selected purposively to participate in this study. Life skills education were conduted for 3 months, every week for 6 hours. At the end of the intervention adolescent’s ambassadors were formed called ”Narsis” to share and educate their peers. Data were analyzed by univariate, independent t-test mann whitney and paired t-test. The findings show that there was significant influence on providing lifeskills education to adolescent’s knowledge, attitudes, self efficacy and prevention health risk behaviour at the intervention group. Whilst, there was only a slight increase on knowledge and significantly decrease in attitudes and self-efficacy including the prevention risk behaviors of adolescents at control group. It is recommended that adolescents are necessary to provide intensive and comprehensive life skills education to prevent their risk behaviours.